Enemy child : the story of Norman Mineta, a boy imprisoned in a Japanese American internment camp during World War II - Warren, Andrea (Margaret Ferguson Books : Holiday House, 2019)
Provides an illustrated biography discussing the life and career of former U.S. congressman Norman Mineta. Describes how ten-year-old Norman and his family were interned at Heart Mountain Internment Camp during World War II, and how his experiences there gave him a spirit of public service. Details how he became the first Asian mayor of a major city then served ten terms in the U.S. House of Representatives where he was instrumental in passing the Civil Liberties Act of 1988. Chronicles the history of Asian immigration to put the internment into historical context, and explores the lasting legacy of the government's policy of imprisoning Japanese immigrants. Includes black-and-white photographs throughout.